The Striking Presence of Absence: A Portrait of Mette Ingvartsen - Bork Petersen, Franziska; Butte, Maren (Peripeti, 2025)
A Portrait of Mette Ingvartsen. When does something stop being dance? How far can you take choreography before it becomes an installation or a performance piece? What is choreography in the expanded field – between the arts and between (bodily) movement and discourse? How can one shift the agency of movement? Mette Ingvartsen explores the ontological status of dance and the political implications this entails.